2005
DOI: 10.1103/physrevlett.94.238103
|View full text |Cite
|
Sign up to set email alerts
|

Role of Delays in Shaping Spatiotemporal Dynamics of Neuronal Activity in Large Networks

Abstract: We study the effect of delays on the dynamics of large networks of neurons. We show that delays give rise to a wealth of bifurcations and to a rich phase diagram, which includes oscillatory bumps, traveling waves, lurching waves, standing waves arising via a period-doubling bifurcation, aperiodic regimes, and regimes of multistability. We study the existence and the stability of the various dynamical patterns analytically and numerically in a simplified rate model as a function of the interaction parameters. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
253
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(267 citation statements)
references
References 21 publications
13
253
1
Order By: Relevance
“…These authors modelled heterogeneity by putting a direct connection from one part of the domain to another and studied the effect of varying the length of this connection. Roxin et al (2005) recently studied a generalisation of a neural field model first presented by Hansel & Sompolinsky (1998) in which there is a fixed delay in the nonlinear term, as opposed to the space-dependent delays that we have. This delay is meant to mimic those due to synaptic and dendritic processing.…”
Section: Discussionmentioning
confidence: 99%
“…These authors modelled heterogeneity by putting a direct connection from one part of the domain to another and studied the effect of varying the length of this connection. Roxin et al (2005) recently studied a generalisation of a neural field model first presented by Hansel & Sompolinsky (1998) in which there is a fixed delay in the nonlinear term, as opposed to the space-dependent delays that we have. This delay is meant to mimic those due to synaptic and dendritic processing.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, if one wants to uncover the dynamics beyond numerical investigations, one is often restricted to mean field theoretical arguments or focuses on globally connected networks or on networks of simple local topology. [2][3][4][5][6][7][8][9][10][11] Here we follow the simple and very useful approach of Mirollo and Strogatz 12 to represent the state of a onedimensional ͑neural͒ oscillator not by its membrane potential, but by a phase that encodes the time to the next spike in the absence of any interactions. In the limit of infinitely fast processing of incoming signals ͑post-synaptic currents͒, the nonlinear interactions can then be treated analytically in an exact manner.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the CPG is treated as the proprioception from the musculoskeletal system and is fed back to the basal ganglia. The researchers have already revealed that time delays can gradually affect the spatio-temporal dynamics in networks of coupled neurons (Roxin et al 2005). Therefore, when the CPG signal is sent to the basal ganglia, the time delay should be considered.…”
Section: Introductionmentioning
confidence: 99%